Identifying Key Correlates of Social Well-Being among Canadian Armed Forces Veterans: An Analysis of the 2016 Life after Service Study. (2nd March 2022) - Born, Jennifer; Lee, Jennifer E. C.; MacLean, Mary Beth; Sweet, Jill; Van Til, Linda
Abstract: Many Veterans experience disruptions to their social connections during military to civilian transition. As low social support has been associated with difficulties adjusting to civilian life, there is value in better understanding social support in Veteran populations. The purpose of this study was to identify correlates of social support among recent Canadian Armed Forces (CAF) Veterans. Data were collected as part of the 2016 Life After Service Survey, which was administered to a sample of CAF Regular Force Veterans. This study focuses on more recently released Veterans, 5 years prior to the survey (n = 1, 723) to better reflect the impact of transitioning to civilian life. Social support was measured using the 10-item Social Provision Scale. Regression models examined the relative associations of individual, release, and post-transition characteristics (i.e., family/household composition and main activity) with social support. Models explained up to 23% of the variance in social support. Lower social support was associated with being: male, older, of noncommissioned rank at release, and released involuntarily ( p ≤ .05). Family/household composition, most notably living with a partner, was also associated with greater social support, especially among Veterans who were not in the workforce. Veterans' main activity in the last year explained the most variance in social support, with a strong association noted for satisfaction with one's main activity ( p ≤ .001). Social support is an important and modifiable factor in the transition to civilian life. Results point to specific subgroups who may be at risk for low social support after military service. Supplemental data for this article is available online at https://doi.org/10.1080/21635781.2021.2007182 .